Synthesis, characterization and analytical study of new imine compounds - ثلاج ناصر (Latakia University Journal -Medical Sciences Series, 2022)
Three compounds, 2,5-dimethyl-4-((4-nitrobenzylidene) amino) phenol (A1),N,N’-([1,1’-biphenyl]-4,4’-diyl)bis(1-(2,4-dimethoxyphenyl)methanimine (A2) and 4,4’-(([1,1’-biphenyl]-4,4’-diylbis(azaneylylidene))bis (methaneylylidene))bis(2-methoxyphenol) (A3), were synthesized and characterized using mass spectrometry, 1H-NMR spectroscopy, and IR spectroscopy. Then, the effects of solvents and pH on the UV-Visible spectrum of these compounds were studied. With the change of the used solvent, the spectra of A3 and A2 had additional absorption bands appeared around 360-370nm using solvents such as methanol and DMSO. The results of pH effects on the synthesized compound spectra in a group of buffer solutions showed that the spectrum of (A1) and (A2) were not affected by the change in pH medium, while the compound (A3) showed a significant change in both Acidic and basic medium. The ionization constants for (A3) were calculated using the half-height method. An equilibrium diagram was proposed to demonstrate the ionization of (A3).